Telaah Kritis Akad Musyarakah Mutanaqisah - Muh Turizal Husein (Al Maal: Journal of Islamic Economics and Banking, 2019)
Since the opening of the MEA door in 2015 to 2020, it will be colored by a strategy competition and a tighter level of financial services business competition. Sharia Banking products based on partnerships with "profit-loss sharing" such as Musyarakah currently have not shown significant growth like other products. One of the musyarakah derivative contracts that has the potential to be practiced as an innovation product in Islamic banking is the musyarakah mutanaqisa contract. This study examines the need for living space for customers by using musyarakah mutanaqisa agreement and musyarakah mutanaqisa practice in Indonesia. This study uses a qualitative approach with descriptive analysis design. In Indonesia, only a few Sharia Banks have offered financing products with mutanaqisa musyarakah contracts, namely Sharia Maybank, Panin Sharia Bank, Mega Syariah Bank and Bank Muamalat. Of the four BUSs, the products they offer have ownership of assets namely home ownership and vehicles. But in their practice they still give customers the choice in choosing, which contract they will use. such as murabahah contracts in home ownership products and vehicles.Keywords: Musyarakah, Mutanaqisa, Profit, Banks